2021
DOI: 10.5194/agile-giss-2-25-2021
|View full text |Cite
|
Sign up to set email alerts
|

A Geo-Dashboard Concept for the Interactively Linked Visualization of Provenance and Data Quality for Geospatial Datasets

Abstract: Abstract. In Earth System Sciences, a data-driven research domain, several communities discuss the importance, guidance and implementation of making research data findable, accessible, interoperable, and reusable. To foster these principles, in particular to support reusability, users need easy-to-use user interfaces with meaningful visualizations for detailed metainformation, e.g. on dataset’s origin and quality. However, visualization tools to facilitate the evaluation of fitness for use of ESS research data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For example, (Kalantari et al, 2014) propose a prototype where volunteers can create metadata by sharing their notes and analyzing the keywords used in the user's search. Finally, we found that most of the quality metadata is for image datasets (Figgemeier et al (2021), Wagner et al (2021)).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, (Kalantari et al, 2014) propose a prototype where volunteers can create metadata by sharing their notes and analyzing the keywords used in the user's search. Finally, we found that most of the quality metadata is for image datasets (Figgemeier et al (2021), Wagner et al (2021)).…”
Section: Introductionmentioning
confidence: 89%
“…For example, in France, the National Council for Geographic Information (NCGI) offers a tool to evaluate datasets by assigning stars from 1 to 5 according to the geographic data quality indicators of the ISO 19157:2013. Metadata visualisation solutions such as those proposed by the GeoViQua project 1 for sensor data (Nüst and Lush (2019)) or by (Figgemeier et al (2021)) to visualise the provenance metadata of a dataset, a complementary information to quality, in the form of a graph, also help users to measure the usability of a dataset.…”
Section: Introductionmentioning
confidence: 99%
“…3), and a map view (No. 4) (Figgemeier et al., 2021). Based on a linked approach, the content of each of the four mentioned widgets dynamically adapts depending on the user's selection.…”
Section: Approaches and Pilots To Integrate Core Software Components ...mentioning
confidence: 99%
“…The dashboards that have been generated share the common characteristic of integrating the geographical component of the tourism information, and in this context, they are referred to as geo-dashboards [25]. Geo-dashboards are embedded in geospatial business intelligence (GBI), which is a fusion of technologies and practices that combines geospatial analysis with business intelligence.…”
Section: Introductionmentioning
confidence: 99%